Association between husband support and compliance with post-cryotherapy requirements among mothers in Tabanan District, Bali - Gede Ngurah Upadana; Anak Agung Sagung Sawitri; I Nyoman Mangku Karmaya (Universitas Udayana, 2019)
Background and purpose: Cervical cancer is a major global health problem for women, with most of cases occurring in developing countries. Visual inspection with acetic acid (VIA) is one method for screening precancerous cervical lesions which can then be followed up with cryotherapy. The success of cryotherapy is influenced by many factors including maternal compliance to meet the clinical requirements after cryotherapy. This study aims to determine the association between husband’s support and mother’s compliance with post-cryotherapy requirements. Methods: A cross-sectional study was conducted on 142 mothers with positive VIA test results and had received cryotherapy in six Tabanan public health centers (PHCs) consisting of four PHCs in urban areas and two PHCs in rural areas. All mothers who underwent cryotherapy during 2017 were selected as samples. Data were collected through face-to-face interviews in each respondent’s home using a questionnaire. The information collected was four post-cryotherapy requirements consisting of sexual abstinence, on schedule follow-up examinations, compliance to the recommended antibiotic use, not using topical vaginal medication and husband’s support. Husband’s support measured by 11 questions consisted of psychological, social and environmental support. Bivariate analysis was performed with chi-square and multivariate analysis with logistic regression. Results: This study shows that only 39.4% of respondents were compliant to meet the four post cryotherapy requirements. As many as 32.4% of mothers had sex within 4 weeks after cryotherapy and 40.1% did not have the follow up examinations on schedule. Husband’s support was significantly associated with maternal compliance in the form of asking about respondent’s health condition with AOR=6.658 (95%CI: 1.794-24.702) and not asking for sex with AOR=4.151 (95%CI: 1.491-11.556). Conclusion: Mother’s compliance with the four requirements after cryotherapy remains low and the husband’s support has a role in increasing maternal compliance. Education on post cryotherapy requirements needs to be improved particularly in regards to the role of the husband.